Pemodelan Matematis Absorpsi Kimia Gas Formaldehiodengan Larutan Urea. - Perpustakaan UGM, i-lib ([Yogyakarta] : Center For Food and Nutritions Studies Gadjah Mada University, 1999)
ABSTRAKS Chemical absorption of formaldehyde by urea solution in a tower equipped with Sieve tray and packed bed was investigated mathematically. Variables studied were gas flow rate, gas inlet temperature, pressure of the system and concentration of water vapor and formaldehyde in the feed gas. The results showed that the process was controlled by mass transfer. The temperature of the gas and gas flow rate didn't affect the process significantly. On the other hand, the pressure and concentration of water vapor and formaldehyde in the feed gas had strong effect to the product. The absorption was very effective if the pressure and concentration of water vapor in the feed gas were relatively low.